Detection of HPV16 in cell lines deriving from cervical and head and neck cancer using a genosensor made with a DNA probe on a layer-by-layer matrix. (18th September 2020) - Soares, Juliana Coatrini; Melendez, Matias Eliseo; Soares, Andrey Coatrini; Arantes, Lidia Maria Rebolho Batista; Rodrigues, Valquiria da Cruz; Carvalho, Andre Lopes; Reis, Rui Manuel; Mattoso, Luiz Henrique C.; Oliveira Jr, Osvaldo N.
Abstract : Electrode modified with chitosan, carbon nanotubes and a layer of cpHPV16 DNA probe to which ssHPV16 DNA binds. Abstract : Detection of human papillomavirus 16 (HPV16) is essential for the diagnosis of cervix and head and neck cancer, which has prompted the development of biosensors to replace the sophisticated molecular techniques. In this paper, we employ a genosensor made with a HPV16 DNA probe (cpHPV16) immobilized on a layer-by-layer (LbL) film of chitosan and carbon nanotubes to detect a complementary sequence HPV16 oligo (ssHPV16). In addition to employing impedance spectroscopy, which has already been used in the literature, we detect ssHPV16 in buffer samples and in cancer cell line samples with UV-vis. spectroscopy. The limit of detection was 18.5 pmol L −1 in impedance spectroscopy measurements and 10.9 pmol L −1 in UV-vis measurements. Distinction of the various ssHPV16 concentrations and of the cancer cell line samples CasKi, SiHa, UMSCC-47, UM-SCC104 and 93-VU147T with both electrical and optical data could be made with the multidimensional projection technique referred to as interactive document mapping (IDMAP), with which we could confirm the absence of false positives by testing cell lines that did not contain ssHPV16 (JHU12, JHU13 and JHU28). The hybridization between cpHPV16 and ssHPV16 responsible for the biosensing was verified with polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS), while the concentration dependence could be modeled with a double Freundlich function. The use of optical absorbance measurements to detect ssHPV16 is promising toward a simple colorimetric detection.